2020
DOI: 10.3390/ijms21165749
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Gene Expression in the Parabrachial and Amygdala of Diestrus and Proestrus Female Rats after Orofacial Varicella Zoster Injection

Abstract: The orofacial pain pathway projects to the parabrachial and amygdala, and sex steroids have been shown to affect neuronal activity in these regions. GABA positive cells in the amygdala are influenced by sex steroid metabolites to affect pain, and sex steroids have been shown to alter the expression of genes in the parabrachial, changing neuronal excitability. Mechanisms by which sex steroids affect amygdala and parabrachial signaling are unclear. The expression of genes in the parabrachial and amygdala in dies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…previously in the amygdala (Liu et al, 2021;Stumpf & O'Brien, 1987) and its expression was shown to be elevated in proestrus rats during the pain response to chicken pox infection (Hornung et al, 2020) and S2), largely consistent with a previous report (Kim et al, 2017).…”
Section: Biological Insightssupporting
confidence: 90%
“…previously in the amygdala (Liu et al, 2021;Stumpf & O'Brien, 1987) and its expression was shown to be elevated in proestrus rats during the pain response to chicken pox infection (Hornung et al, 2020) and S2), largely consistent with a previous report (Kim et al, 2017).…”
Section: Biological Insightssupporting
confidence: 90%
“…In female rats expression of Nrxn3α was elevated at proestrus in the central amygdala and the amount of transcript was correlated to the concentration of plasma estradiol ( Hornung et al, 2020 ). In this study attenuating Nrxn3 expression within the central amygdala increased VZV associated orofacial pain after VZV was injected into the vibrissae pad of the rat.…”
Section: Discussionmentioning
confidence: 99%
“…The pain response is due, in part, to expression of early viral proteins ( Guedon et al, 2014 ) and it has been shown that complete replication and production of new virus particles is not required for the pain response ( Warner et al, 2021 ). Recently our lab reported neurexin 3α (Nrxn3α) was expressed in the central amygdala and parabrachial and that expression differed during the estrous cycle in rats with VZV induced pain ( Hornung et al, 2020 ). Nrxn3α expression was elevated in the central amygdala of proestrus female rats vs. rats in diestrus.…”
Section: Introductionmentioning
confidence: 99%
“…VZV parental Oka (pOka) is a wild-type varicella isolate from which the current live attenuated vaccines were derived [46]. It has been established that pOka can induce both mechanical and thermal hypersensitivity in rat models of PHN [31][32][33][34][35][36][37][38] and was used as a positive control in all studies. Recombinant viruses were derived from a pOka bacterial-artificial chromosome (BAC) which contains a self-excisable BAC replicon [47] that was subsequently corrected for two spurious mutations in the VZV ORF40 and ORF50 genes and contained an N terminal GFP reporter fused to ORF23 [48].…”
Section: Cells and Virusesmentioning
confidence: 99%
“…It was then demonstrated by multiple groups that Wistar and Sprague-Dawley rat strains inoculated with VZV at the footpad develop prolonged signs of pain that could serve as preclinical models for exploring mechanisms and treatment strategies for PHN [22]. The models involve subcutaneous inoculation of cell-associated VZV into the rat hind footpad [26][27][28][29][30][31][32] or more recently, the whisker pad [33][34][35][36][37][38]. While animals show no outward signs of skin infection, inflammatory response, or disease, they develop nocifensive behaviors lasting several weeks.…”
Section: Introductionmentioning
confidence: 99%